Energy transfer and color‐tunable emission in Ba2Y2Si4O13:Bi3+, Eu3+ phosphors. Issue 4 (19th September 2018) - Song, WeiHui; Chen, XueYan; Teng, LiMing; Zheng, ZhiGang; Wen, Jun; Hu, FangFang; Wei, RongFei; Chen, LiPing; Guo, Hai
Abstract: Single‐composition Ba2 Y2 Si4 O13 :Bi 3+, Eu 3+ (BYSO:Bi 3+, Eu 3+ ) phosphors with color‐tunable and white emission were prepared by conventional high temperature solid‐state reaction method. The structural and luminescent properties of these phosphors were thoroughly investigated through X‐ray diffraction, photoluminescence, and decay curves. BYSO:Bi 3+ phosphors show two excitation peaks at 342 and 373 nm, and give two emission peaks at 414 and 503 nm, respectively, indicating that there are two sites of Bi 3+ in BYSO. The energy transfer from Bi 3+ to Eu 3+ was investigated in detail. Varied hues from blue (chromaticity coordinate [0.219, 0.350]) to white (0.288, 0.350) and orange‐red light (0.644, 0.341) can be generated by adjusting the content of Eu 3+ . Pure white light emission (0.311, 0.338) can be obtained under the excitation of 355 nm in BYSO:3%Bi 3+, 20%Eu 3+ phosphor. Besides, BYSO:Bi 3+, Eu 3+ phosphors exhibit distinct thermal quenching properties, whose emission intensity at 473 K is 82.6% of that at 298 K. Our results indicate that BYSO:Bi 3+, Eu 3+ may be applied as conversion phosphors for n‐UV‐based W‐LEDs.